Reator em batelada sequencial (RSB) para o tratamento de efluentes de pequenas e médias indústrias de laticínios - Santos, Vanessa Rita dos (2009)
The accomplishment of environmental legislation in the attending of effluents releasing standards in the superficial hydrous bodies is essential to the preservation of water resources. The dairy industries, have presented a high consumption of water on its various activities within the industry and consequently a high generation of effluents per unit produced. These effluents generated have on its composition organic matter, nitrogen and phosphorus. The in batch reactors have been modified to achieve the removal of these. This work presents the study accomplished in sequential batch reactor for the treatment of synthetic effluent from dairy, aiming to study the use of this reactor in the removal of chemical oxygen demand (COD), total ammonia nitrogen (Nt) and total phosphorus (Pt). The amount of biomass placed in the reactor ranged from 1 000 mg/L to 3 500 mg/L of total suspended solids. The sedimentation of biomass lasted 45 min at each end of operation. The reactor worked up to 6 h of operation. The samples for analysis of COD, total ammonia nitrogen, phosphorus, sediment solids, total suspended solids, pH and temperature were collected at each start (0 h) and end (6 h) of operation. The samples for analysis of COD, temperature and pH were collected every 2 h until complete 6 hours of operation. The aeration was constant in this period of operation and the flow of air was maintained at 1.8 L/min. The concentrations of milk were 1 000 mg/L, 2 000 mg/L, 3 000 mg/L, 4 000 mg/L, 5 000 mg/L and 6 000 mg/L for the results these concentrations were transformed into concentrations of COD correspondents. The best efficiency of removal of chemical oxygen demand, total ammonia nitrogen and total phosphorus were from 94 %, 75 % and 82 % respectively. The sequential batch reactor is an important alternative for small and medium dairy